1986
DOI: 10.1161/01.hyp.8.11.1003
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic alpha 1- and alpha 2-adrenergic receptors in adrenergic control of capacitance vessel tone in vivo.

Abstract: SUMMARY The involvement of postsynaptic a 2 -adrenergic receptors in the adrenergic constriction of the capacitance vessels was studied in anesthetized, spontaneously breathing dogs under ganglionic blockade (hexamethonium, 10 mg/kg + 10 mg/kg/hr; methylatropine, 0.5 mg/kg). Effective vascular compliance was measured as an indicator of venous tone (blood volume was varied by ± 4 ml/kg in an 11-minute cycle of infusion, withdrawal, withdrawal, and reinfusion) and was calculated from the correlation between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…(Sigma Chemical, Munich, FRG) and by semilogarithmic extrapolation of arterial plasma concentration at injection time from several plasma samples, analyzed photometrically at 578 nm, obtained 10-40 minutes after the injection. [12][13][14][15][16][17][18] hours after the final diclofenac injection, these dogs were anesthetized and prepared for measurement of compliance under ganglionic and ,Badrenergic blockade as described for protocols 1-7. Compared with the effects of norepinephrine infusion in the same model, the COI in protocols 1 and 2 caused preferential venoconstriction.…”
Section: Measurementsmentioning
confidence: 99%
“…(Sigma Chemical, Munich, FRG) and by semilogarithmic extrapolation of arterial plasma concentration at injection time from several plasma samples, analyzed photometrically at 578 nm, obtained 10-40 minutes after the injection. [12][13][14][15][16][17][18] hours after the final diclofenac injection, these dogs were anesthetized and prepared for measurement of compliance under ganglionic and ,Badrenergic blockade as described for protocols 1-7. Compared with the effects of norepinephrine infusion in the same model, the COI in protocols 1 and 2 caused preferential venoconstriction.…”
Section: Measurementsmentioning
confidence: 99%
“…"-' 5 A recently published study by Segstro and Greenway 13 demonstrated that the hepatic volume of the cat, monitored plethysmographically, decreases in the presence of an a 2 -agonist. The finding by Eisner et al 20 that UK 14,304 decreases effective vascular compliance in the dog with ganglionic blockade also provides evidence for a direct hemodynamic effect of an a 2 -agonist on the venous circulation. Evidence for the decrease in vascular capacitance found in the present study was not seen in the canine studies by Zandberg et al 18 and by Woodman and Vatner.…”
Section: Discussionmentioning
confidence: 85%
“…18 Similarly, after ganglionic blockade and /3-adrenergic receptor and muscarinic blockade in conscious dogs, 19 B-HT 920 did not increase cardiac output. However, a recent study by Eisner et al 20 has shown in anesthetized, spontaneously breathing dogs with ganglionic blockade that effective vascular compliance was higher and central venous pressure lower than in conscious dogs without ganglionic blockade. The administration of the a 2 -agonist UK 14,304 lowered compliance and increased central venous pressure to levels found in conscious dogs.…”
mentioning
confidence: 95%
“…However, previ ous studies (13,14) have shown that these changes were in dependent of EVS. (2) LNNA-induced increase in central venous pressure may also alter EVS.…”
Section: Discussionmentioning
confidence: 98%